Constructional approaches to syntactic structures in German - Boas, Hans Christian, 1971-; Ziem, Alexander (Trends in linguistics. Studies and monographs ;, 2018)
"This book provides a state of the art collection of constructional research on argument structure constructions in German. The volume is unique in that it offers an easily accessible, yet comprehensive and sophisticated variety of papers. Moreover, various of the papers make explicit connections between grammatical constructions and the concept of valency which has figured quite prominently in Germanic linguistics over the past half century"--